2022
DOI: 10.3390/v14030586
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Herpesviridae Protein Kinase (CHPK) of Gallid alphaherpesvirus 3 (GaHV3) Is Required for Horizontal Spread and Natural Infection in Chickens

Abstract: We have formerly identified the conserved herpesvirus protein kinase (CHPK) as essential for horizontal transmission of Marek’s disease virus (MDV). Thus far, it has been confirmed that the mutation of the invariant lysine (K) of CHPKs abrogates kinase activity and that CHPK activity is required for MDV horizontal transmission. Since CHPK is conserved among all members of the Herpesviridae, we hypothesized that CHPK, and specifically its kinase activity, is important for the horizontal transmission of other he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…A summary of viruses used in this study are shown along with plaques formed during coinfection in cell culture showing both viruses present in the mixture ( Figure 2 ). Chickens were inoculated with a mixture of MDV-NT (lacking MDV gC) and vacMD-T (vacMD expressing MDV gC) or vacMD-NT (vacMD that has CHPK mutated) of which all viruses have previously been published for their transmissibility [ 17 , 18 , 20 ]. MDV-NT lacks gC, required for transmission and expresses enhances green fluorescent protein (eGFP), while both vacMD-T and vacMD-NT express monomeric red fluorescent protein (mRFP) allowing us to differentiate each virus in cell culture and in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A summary of viruses used in this study are shown along with plaques formed during coinfection in cell culture showing both viruses present in the mixture ( Figure 2 ). Chickens were inoculated with a mixture of MDV-NT (lacking MDV gC) and vacMD-T (vacMD expressing MDV gC) or vacMD-NT (vacMD that has CHPK mutated) of which all viruses have previously been published for their transmissibility [ 17 , 18 , 20 ]. MDV-NT lacks gC, required for transmission and expresses enhances green fluorescent protein (eGFP), while both vacMD-T and vacMD-NT express monomeric red fluorescent protein (mRFP) allowing us to differentiate each virus in cell culture and in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…MDV-NT lacks gC (MDV δgc) that is required for transmission [ 8 , 9 , 23 ]. vacMD was rendered NT through mutation of its CHPK activity by mutation of the invariant lysine (K157A) that is required for transmission [ 18 ]. vacMD-T expresses MDV gC in place of its gC [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations